Releyendo a Sawamura Y, Abe H Hypoglossal–facial nerve side-to-end anastomosis for preservation of hypoglossal function: results of delayed treatment with a new technique J Neurosurg. 1997; 86:203–6 - Bustamante, Jorge (Revista Argentina de Neurocirugía, 2021)
-
Keywords: -